Tinjauan Etika Bisnis Syariah Pada Manajemen Laba - Widya Sari; Naning Fatmawatie (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This research aims to deepen understanding of the Review of Sharia Business Ethics in Profit Management. The method applied in this research is a descriptive method with a qualitative descriptive research type, which utilizes a literature study approach. The data source used in this research is secondary data. Research results show that earnings management is a controversial practice in the business world, which involves efforts to manipulate company profits for various purposes. Some managers use earnings management to maximize profits (Income Creasing) or avoid taxes (Income Decreasing). This practice goes against the principles of Sharia business ethics because it does not emphasize values such as honesty and trust. Earnings management can also harm other parties, which makes it even more controversial. In the context of Islamic business, it is important to prioritize Sharia business ethical values in all aspects of business, including profit management. This is important to ensure that business practices are carried out by Islamic principles and provide fair benefits for all parties involved.